Razumevanje modernizma v novejši poljski literarni vedi - Rezoničnik, Lidija (Primerjalna književnost, 2017)
Based on existing literary studies, this article presents the development of understanding and discussions about Polish modernism. Polish literary criticism adopted the concept of modernity at the end of the 19th century from Western Europe. The term modernism appeared in Polish literary studies in first half of the 20th century. First it was used for defining literature at the turn of the 19th and 20th century - sometimes it denoted the initial literary phase of the so-called Young Poland (K. Wyka) or, if used by the literary criticism between the two world wars, the period of Young Poland as a whole (1890-1918). Newest literary studies (R. Nycz, W. Bolecki), particularly after 1990, discuss Polish literature of the 20th century from Anglo-Saxon perspective and place modernism in the context of the Central- and East European area with consideration of regional socio-political and cultural-historical factors (i.e. Poland as non-existent country, independence since 1918, World War II, communism, emigration). R. Nycz, W. Bolecki and M. Dąbrowski specify some main characteristics of the Polish modernism, namely: independence and rejection of utilitarianism in literature, as well as essentialism and conflict between modernity and modernization. Due to temporarily obligatory socialist realism Polish modernist literary works were not written just in Poland but also in exile, where certain authors maintained continuity of the Polish modernism. Contemporary Polish literary studies combine both branches of modernism ("domestic" and "exilic"). In addition, three subperiods of Polish modernism have been defined as: Young Poland modernism, avant-garde and after 1945 modernism.
Keywords: avant.garde; Bolecki, Włodzimierz; literarna avantgarda; literarne smeri; literary periods; mlada Poljska; modernism; modernizem; Nycz, Rysyard; Polish literary studies; Polish literature; poljska književnost; poljska literarna veda; Young Poland